Loop-mediated isothermal amplification (LAMP) in the respiratory specimens for the diagnosis of pediatric pulmonary tuberculosis: A pilot study. Issue 8 (August 2020) - Sreedeep, K.S.; Sethi, Sunil; Yadav, Rakesh; Vaidya, Pankaj C.; Angurana, Suresh Kumar; Saini, Aastha; Mehra, Nancy; Singh, Meenu
Abstract: Background: Loop-mediated isothermal amplification (LAMP) assay is a novel molecular diagnostic technique that can be used for the diagnosis of tuberculosis (TB). It is most suited for developing countries as it is rapid, inexpensive, highly sensitive, requiring minimal infrastructure, training and manpower. Studies in pediatric TB are lacking. We evaluated LAMP in the diagnosis of pediatric pulmonary TB. Methodology: This was a cross-sectional analytical study conducted at a tertiary care teaching hospital in North India from July 2014 to June 2015 involving 60 children with suspected pulmonary TB. Respiratory specimens (sputum, gastric lavage, bronchoalveolar lavage and/or endotracheal aspirates) were collected and subjected to BACTEC MGIT 960 culture, IS6110 PCR, and LAMP assay targeting IS6110 gene of Mycobacterium tuberculosis . Results: Thirty seven children had confirmed and probable TB according to the composite reference standard (CRS). Among all the 3 tests used for diagnosis of Pulmonary TB, LAMP had highest sensitivity (37.8%) followed by PCR (27%), and culture (21.6%) when compared against the predefined CRS. Culture had maximum specificity of 100%; and PCR, and LAMP had specificity of 95–96%. The sensitivity, specificity, PPV, and NPV of LAMP against culture as reference standard were 75%, 72.4%, 42.9%, and 91.3% respectively. Similarly sensitivity, specificity, PPV, and NPV of PCR against culture as reference standard were 75%, 86.2%, 60%, and 86.2% respectively. On combining LAMP with culture, sensitivity increased to 45.7% (7.8% increase, p = 0.04). Conclusion: We noted that LAMP had highest sensitivity when compared to culture and PCR and comparable specificity.